Heatwaves: An invisible risk in UK policy and research. Issue 116 (February 2021) - Brimicombe, Chloe; Porter, James J.; Di Napoli, Claudia; Pappenberger, Florian; Cornforth, Rosalind; Petty, Celia; Cloke, Hannah L.
Highlights: The UK policy and guidance for heatwaves is inadequate. 'Silo' thinking in heatwave research hinders robust policymaking. Heatwaves are often framed only as a health sector risk. More research, across different sectors, is urgently needed. Abstract: In 2019, a heatwave – an unusual extended period of hot weather – broke the UK's highest recorded temperature of 38.7 °C set in 2003. Of concern is that for summer 2019, this resulted in 892 excess deaths. With the intensity and frequency of UK heatwaves projected to increase, and summer temperatures predicted to be 5 °C hotter by 2070, urgent action is needed to prepare for, and adapt to, the changes now and to come. Yet it remains unclear what actions are needed and by whom. In response, a systematic literature review of UK heatwaves peer-reviewed publications, inclusive of keyword criteria (total papers returned = 183), was conducted to understand what lessons have been learnt and what needs to happen next. Our research shows that heatwaves remain largely an invisible risk in the UK. Communication over what UK residents should do, the support needed to make changes, and their capacity to enact those changes, is often lacking. In turn, there is an inherent bias where research focuses too narrowly on the health and building sectors over other critical sectors, such as agriculture. An increased amount of action and leadership is therefore necessary from the UK government to address this.